REMAINING STRENGTH AND LIFE ANALYSIS FOR SINGLE DEFECT, INTERACTION DEFECT, AND COMPLEX SHAPE DEFECT IN CORRODED PIPELINE - FERDIAN CHRISANTO (NIM : 13107038); Dosen Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, RICKY
In oil and gas industry, pipelines have often been used to transport and distribute fluids. Degradation in pipeline always happen during the operation and can’t be avoided. One of the most common degradation is caused by corrosion. It leads to a pipeline failure which has some negative effects to public safety and environment.Therefore, it needs an action to control and prevent development of the corrosion as a failure. This action is called pipeline integrity management. Strength and integrity assessment is one of the core activity in integrity management process. The focus in this final project is to conduct pipeline strength and integrity assessment for corroded pipeline. This analysis based on DNV-RP-F101 processes some data from intelligent pigging inspection that have been conducted for Lembak – Simpang Y gas pipeline which lays on southern Sumatera. Corrosion defects assessment are conducted in twomethods those are method A – Calibrated Safety Factor and method B – Allowable Stress Approach. Based on these methods, the corrosion defects are analyzed as a single defects, interacting defects, and complex shape defects. Interacting defect is a combination of some adjacent single defects that collectively affect the pipeline’s remaining strength. Complex shape defect is a cluster of some really close single defects that acts as one defect. The method A assessment results show some critical points those are located at absolute distance km 45,287 for single defect, km 2,665 for interacting defect, and km 5,731 for complex shape defect. According to method B assessment results, some obtained critical point is km 45,287 for single defect, km 44,956 for interacting defect, and km 5,731 for complex shape defect.